THE INTENTION, GENRE, DATING AND PROVENANCE OF 2 AND 4 MACCABEES - Cook, Johann (Journal for Semitics, 2017)
<span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 10pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: EN-ZA; mso-bidi-language: AR-SA;">There is a relationship between 2 and 4 Maccabees. The author of 4 Maccabees clearly made use of 2 Maccabees. There are also differences between these writings. These differences pertain to inter alia genre, intention and provenance. Suitable criteria need to be formulated to address this issue. In order to determine the provenance of these individual books, this paper analyses internal (linguistic) and external (historical) criteria